Remote Monitoring of Process in Industry Using ARM7 and Wireless Sensor Network - Ramtekkar, Harshal; Meshram, Divya (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Industries are setting new standards for processes, which are crucial to meet the challenges. These challenges include gamut of processes for monitoring, precision, safety and many more. In this paper the monitoring of physical parameter at realtime environment is proposed. The scheme implemented provides remote monitoring of process in industry using ARM7 controllerand Wireless Sensor Network. For long distance monitoring at working place we used ZigBee which will be responsible fortransmitting and receiving the sensed values from the parallel processors. With the help of ARM7 controller the data of interesti.e. variation in light, gas and temperature is sensed and transmitted to remote mobile phone and PDA’s, which makes itremote monitoring application. Practical implementation of the scheme makes its use apparent for monitoring.